Northern Ghana final-year nurses' attitudes towards nursing and remaining post qualification - Atuut Abugri; Mary-Ann Jarvis (AOSIS, 2018)
Background: Recruitment and retention concerns nursing globally, including Ghana, as the country attempts to meet health demands. A link exists between nursing students' attitudes towards nursing and decisions to enter, remain in or withdraw from the profession. Objectives: To describe northern Ghana final-year student nurses' current attitudes towards nursing and remaining in nursing post qualification. Method: Non-experimental quantitative descriptive design used convenient sampling targeting final third-year student nurses (n = 80) studying towards a Diploma in Registered General Nursing in a northern Ghana college (N = 220). Data were gathered using the attitude dimension of a self-administered questionnaire, developed by Al-Omar. Results: The response rate was 87.5% (n = 70). Respondents were 20-30 years of age, more men and predominantly from urban areas. The mean attitude dimension score (range 10-50) was 35.41 (SD 4.03) with no skewness (0.37); mean of single-item question about intention to stay in nursing was 3.68 (SD 1.14) with negative skewness (-0.92). Male and urban respondents' attitudes were more positive than those of female respondents. No association was found between attitude score and demographics or intention to stay in nursing, but significant association was found between gender and habitation and attitude categories. Medium positive correlation existed between intent to stay in nursing and attitude score. Pay, travel opportunities and nursing being a challenging career attracted unfavourable attitudes. Conclusion: Ghanaian male student nurses' attitudes are non-typical of general stereotypes held of nurses and gender, suggesting increased recruitment of male nurses. Demographic variables hold a small amount of value in the development of attitudes in Ghanaian nurses.